Advances in Information Retrieval : 38th European Conference on IR Research, ECIR 2016, Padua, Italy, March 20-23, 2016. Proceedings /: 38th European Conference on IR Research, ECIR 2016, Padua, Italy, March 20-23, 2016. Proceedings. (2016) - Unknown
No abstract available